A Japanese case of castration-resistant prostate cancer with BRCA2 and RB1 co-loss and TP53 mutation: a case report - Tomohiro Iwasawa; Takeo Kosaka; Shinya Morita; Shuji Mikami; Kohei Nakamura; Hiroshi Hongo; Hiroshi Nishihara; Mototsugu Oya (BMC, 2022)
Abstract Background Abnormalities in homologous recombination contribute to the aggressive nature of castration-resistant prostate cancer. Retinoblastoma transcriptional corepressor 1 (RB1) and breast cancer 2 (BRCA2) exist close to each other in the same chromosome, and the significance of their concurrent loss has become a hot topic in the field of cancer research. Case presentation A 61-year-old man presented with a chief complaint of a mass on his head and was diagnosed as multiple bone metastases from prostate cancer. He was treated with standard medication, but he died 2 years 6 months after being diagnosed with prostate cancer. Simultaneous biallelic loss of RB1 and BRCA2 as well as a truncating mutation of tumor protein p53 (TP53) were revealed by genomic analysis. Conclusion To our knowledge, this is the first report of castration-resistant prostate cancer (CRPC) with BRCA2 and RB1 co-loss and TP53 mutation. To establish a treatment strategy for highly malignant cases with such multiple genetic features is important.